Agreement Between 10-2 and 24-2C Visual Field Test Protocols for Detecting Glaucomatous Central Visual Field Defects. Issue 6 (June 2021) - Chakravarti, Tutul; Moghadam, Mohamad; Proudfoot, James A.; Weinreb, Robert N.; Bowd, Christopher; Zangwill, Linda M.
Abstract : Precis: Moderate to substantial agreement between 10-2 and 24-2C perimetry for detecting central field defects suggests that adding central test points to the 24-2 protocol may improve efficiency of visual field (VF) testing for glaucoma management. Purpose: The purpose of this study was to assess agreement between Humphrey Visual Field Analyzer 10-2 and 24-2C test protocols for detecting glaucomatous defects in the central 10 degrees of the visual field (CVFDs). Materials and Methods: VFs from 165 eyes of 18 healthy individuals, 12 glaucoma suspects and 62 glaucoma patients who completed 10-2 and 24-2C VF testing protocols within 6 months were included. CVFDs on 10-2 and 24-2C (within the central 22 points) test grids required a cluster of 3 contiguous points with P <5%, 5%, and 1% or <5%, 2%, and 2% within a hemifield on the total deviation (TD) or pattern deviation (PD) plot. Cohen kappa (k) was used to assess agreement between 10-2 and 24-2C test grids in identifying CVFDs. Specificity of each testing strategy was assessed in VFs from healthy eyes. Results: CVFDs in suspect and glaucoma eyes were combined and reported as localized to superior, inferior or both hemifields based on TD and PD plots for 10-2 and 24-2C test grids. Moderate to substantial agreement was observed between 10-2 and 24-2C grids for detecting any CVFD from PD (k=0.551) and TD (k=0.651) plots. Specificity was high in healthy eyes ranging from 0.94 to 1.0 for both test protocols. Conclusion: Substantial agreement for identifying CVFDs using the 24-2C and 10-2 protocols suggests that combining tests by adding central test points to the 24-2 test grid may supplant the need for 2 perimetry regimens for detecting central and peripheral glaucomatous VF damage.